A kind of low water absorption boron nitride ceramic and preparation method thereof

The boron nitride ceramic matrix is ​​processed through boiling and vacuum impregnation processes, and the pores are filled with silicon sol and sintered to remove moisture-absorbing components, which solves the problem of high water absorption of boron nitride ceramics, achieving low water absorption, high density and excellent Dielectric properties and thermal shock resistance.

CN118894739BActive Publication Date: 2025-02-18SHANGHAI FRP RES INST
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411393533.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-18
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The high water absorption rate of existing boron nitride ceramics affects their wave transmission performance, and their performance may be affected in high temperature or high pressure environments.

Method used

Boron nitride ceramic matrix is ​​treated by boiling and vacuum impregnation processes, and pores are filled with silicon sol and sintered to remove moisture-absorbing components, reducing water absorption and increasing density.

Benefits of technology

Boron nitride ceramics with low water absorption, high density, excellent dielectric properties and thermal shock resistance are prepared, which are suitable for aerospace wave-transmissive material components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118894739B_ABST
    Figure CN118894739B_ABST
Patent Text Reader

Abstract

This invention discloses a low-water-absorption boron nitride ceramic and its preparation method, belonging to the field of ceramic preparation. Addressing the problem that the high water absorption rate of existing boron nitride ceramics affects their wave transmission properties, this invention provides a method for preparing low-water-absorption boron nitride ceramics. The method includes boiling and drying a boron nitride ceramic matrix, followed by a first vacuum impregnation in silica sol; in-situ gelation of the boron nitride ceramic matrix immersed in silica sol, followed by gradual heating and drying to remove the surface gel; sintering and a second vacuum impregnation of the boron nitride ceramic matrix after surface gel removal; and drying the boron nitride ceramic matrix after the second vacuum impregnation to obtain the low-water-absorption boron nitride ceramic. The entire preparation process of this invention is simple, controllable, and easy to implement, which is beneficial for industrial production. Furthermore, the prepared boron nitride ceramic exhibits high density, low water absorption, excellent dielectric properties, and thermal shock resistance, making it suitable for preparing aerospace wave-transparent material components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic preparation, and more specifically, relates to a low water absorption boron nitride ceramic and a preparation method thereof. Background Art

[0002] Hexagonal boron nitride (h-BN) ceramics are high-temperature resistant ceramics with great development potential. Their operating temperatures exceed 2800°C in an inert atmosphere and reach up to 900°C in oxygen. They exhibit no softening at high temperatures, are resistant to corrosion from strong acids and alkalis, and possess low thermal expansion coefficients, dielectric constants, and losses. They are used in the manufacture of high-frequency microwave devices such as filters, resonators, and antennas, protecting their proper operation and enjoying widespread application in communications, radar, and navigation. However, because boron nitride is a covalent compound with a high melting point, low solid-phase self-diffusion coefficient, and a lamellar crystal structure, sintering densification is inhibited, resulting in a certain porosity in boron nitride ceramics. Furthermore, the raw powders used to prepare boron nitride ceramics often contain hygroscopic boron oxide, which readily absorbs moisture in high-humidity environments, affecting the dielectric constant and losses, and thus, the wave transmission properties. Therefore, how to seal the pores of boron nitride ceramics without compromising their dielectric properties and strength remains a challenge in the current application of boron nitride ceramics.

[0003] Corresponding improvements have also been made to the above problems. Chinese patent application number CN202410851801.2, published on September 3, 2024, discloses a method for preparing high-density boron nitride ceramic materials at low temperature. Using micron-sized flaky hexagonal boron nitride powder as raw material, a small amount of boric acid aqueous solution is added, and the flaky boron nitride powder is pressed and sintered at room temperature and pressureless at low temperature to promote the rearrangement of the grain structure and low-temperature sintering densification, thereby obtaining high-density boron nitride ceramics (density ≥ 1.90 g / cm3). The disadvantage of this patent is that although the preparation process is simple, it may not be able to fully improve its high-temperature resistance. When used in high-temperature or high-pressure environments, the performance of boron nitride ceramics may be seriously affected, and even cause material failure. Summary of the Invention

[0004] 1. Problems to be solved

[0005] To address the problem of high water absorption in existing boron nitride ceramics, which affects their wave transmission, the present invention provides a low-water-absorption boron nitride ceramic and its preparation method. The entire preparation process is simple, controllable, and easy to implement, facilitating industrial production. The resulting boron nitride ceramic has high density, low water absorption, and excellent dielectric properties and thermal shock resistance, making it suitable for use in the manufacture of wave-transmitting aerospace components.

[0006] 2. Technical solution

[0007] To solve the above problems, the present invention adopts the following technical solutions.

[0008] A method for preparing boron nitride ceramics with low water absorption rate comprises the following steps:

[0009] S1: The boron nitride ceramic substrate is boiled and then dried, and vacuum impregnated in silica sol for the first time;

[0010] S2: cleaning the surface gel of the boron nitride ceramic substrate after the first vacuum impregnation;

[0011] S3: sequentially sintering and vacuum impregnating the boron nitride ceramic substrate after removing the surface gel;

[0012] S4: Drying the boron nitride ceramic substrate after the second vacuum impregnation to obtain a boron nitride ceramic with low water absorption.

[0013] The above technical solution is adopted, by directly boiling the formed boron nitride ceramic matrix, so that the boron oxide in the boron nitride ceramic matrix that is easily absorbing moisture is dissolved and dried in the boiling water, thereby reducing the water absorption rate of the boron nitride ceramic matrix to a certain extent; at the same time, the formed boron nitride ceramic matrix itself has a certain low water absorption rate, and under the premise of having a low water absorption rate, it can complete the conversion to a lower water absorption rate; then it is placed in silica sol for immersion, so that the nano-silica particles in the silica sol are filled into the pores of the boron nitride, reducing the porosity of the boron nitride ceramic matrix; then, sintering is performed to remove the silanol groups on the surface of the silica that are easily absorbing moisture, and a second vacuum impregnation is performed to further reduce the porosity of the boron nitride ceramic, so that the boron nitride has better moisture resistance; the entire process is simple, controllable, easy to implement, and conducive to industrial production. In addition, the prepared boron nitride ceramic has high density, low water absorption, excellent dielectric properties and thermal shock resistance, and can be used to prepare aerospace wave-transparent material components.

[0014] Furthermore, the preparation of the silica sol in step S1 includes dissolving tetraethyl orthosilicate in ethanol and mixing and stirring to obtain a first mixed liquid, adding a second mixed liquid to the first mixed liquid, mixing and stirring, and then standing to obtain silica sol; the second mixed liquid is a mixture of hydrochloric acid and water.

[0015] The above technical solution produces silica sols with a smaller particle size, reaching single-digit nanometers, compared to traditional silica sol preparation methods. Traditional silica sol preparation methods typically have tens of nanometers. Smaller particle sizes facilitate full filling of the pores of boron nitride ceramics, effectively reducing porosity. The silica sol obtained using tetraethyl orthosilicate as the silicon source offers the best performance and a relatively stable process. Adding ethanol as a hydrolysis solvent for tetraethyl orthosilicate does not hinder the hydrolysis and condensation reaction of tetraethyl orthosilicate and is safer than other alcohols. Adding water as a reactant for the hydrolysis of tetraethyl orthosilicate and hydrochloric acid as a hydrolysis catalyst promotes the full completion of the hydrolysis reaction and increases the solid content of the silica sol. Configuring the mixed solution in this order allows for a more complete silica sol preparation reaction.

[0016] Furthermore, the molar ratio of tetraethyl orthosilicate: ethanol: water: hydrochloric acid is 1:4-20:4-8:1.0×10-3-2.0×10-3; and the pH value after adding the second mixed solution is 2-3.

[0017] Using the above technical solution, the performance of the silica sol obtained by adding different solvents, reactants, and catalyst concentrations will vary greatly. By setting a suitable molar ratio of tetraethyl orthosilicate, ethanol, water, and hydrochloric acid, the silica sol finally prepared has a smaller particle size and a more uniform distribution, and has higher stability, while also accelerating the reaction efficiency of the entire preparation process.

[0018] Furthermore, the second mixed liquid is added to the first mixed liquid at a dropping speed of 1 ml / min to 5 ml / min, and the mixing and stirring time after the second mixed liquid is added is 1 hour to 5 hours.

[0019] By adopting the above technical solution, by determining the appropriate dropping speed of the second mixed liquid, it is possible to avoid uneven reaction due to excessively high local concentration caused by excessive dropping acceleration, and unstable reaction due to excessive heat release; it is also possible to avoid extending the entire preparation time due to too slow dropping acceleration; determining the appropriate stirring time of the second mixed liquid can avoid increased energy consumption and reduced production efficiency due to too long stirring time, and avoid uneven mixing due to too short stirring time, which can lead to problems such as uneven particle size distribution and uneven structure after gelation of the silica sol.

[0020] Furthermore, the specific process of removing the gel on the surface of the boron nitride ceramic substrate in step S2 is: using an alkaline solution to adjust the pH value of the silica sol to a weak acidic state to solidify the silica sol in situ gel, and then heating and drying to treat the gel on the surface of the boron nitride ceramic substrate.

[0021] Using this technical solution, the hydrolysis reaction rate of tetraethyl orthosilicate is higher than the polycondensation reaction rate under acidic conditions, producing numerous oligomers and polymers. This is then followed by a single-step hydrolysis reaction under alkaline conditions. Because the hydrolysis and polycondensation rates of the polymers are faster than those of the oligomers under alkaline conditions, the polymer chains continue to grow in all directions, ultimately forming a gel network structure through cross-linking of the colloidal cluster particles. This method produces a gel with a high degree of crosslinking and a strong network structure, which helps maintain and enhance the properties of boron nitride.

[0022] Furthermore, the pH value of the silica sol is adjusted to acidic using a pH adjuster, and the pH adjuster is ammonia water with a concentration of 0.2 mol / L to 0.8 mol / L. After adding ammonia water, the pH value is adjusted to 5 to 7.

[0023] The above technical solution uses ammonia as a pH adjuster to solidify the silica sol in situ. This prevents the volatilization of the solvent during the drying process from causing the silica nanoparticles originally filling the pores to accumulate on the outer surface of the boron nitride, thereby reducing the filling rate of the ceramic's internal pores. Furthermore, ammonia is a weak base, which facilitates the production of silica nanoparticles with uniform morphology, while other strong base systems tend to produce larger and more irregularly shaped nanoparticles. Furthermore, after high-temperature treatment, ammonia does not retain residual alkali metal cations that could affect the dielectric properties of the boron nitride ceramic.

[0024] Furthermore, after the silica sol in-situ gel is solidified, the temperature is raised from room temperature to 100°C; and the boron nitride ceramic matrix after the surface gel is removed is sintered, the sintering temperature is 500°C to 900°C, the heating rate is 5°C / min to 20°C / min, and the holding time is 60min to 240min.

[0025] Furthermore, in step S3, the sintered boron nitride ceramic substrate is vacuum impregnated for the second time with an organic silicone resin, wherein the solid content of the organic silicone resin is 20% to 50% and the viscosity is 3 mPa•s to 25 mPa•s.

[0026] Using the above technical solution, silicone resin is used for the second vacuum impregnation. After the first impregnation with silica sol, the surface of the boron nitride ceramic substrate will be covered with a layer of silicon dioxide formed by the solidification of silica sol. The strong interaction between silicone resin and silicon dioxide can significantly improve the adhesion of the silicone resin layer to the surface of the boron nitride ceramic substrate, forming a dense and continuous protective layer, further reducing the water absorption rate of the boron nitride ceramic.

[0027] Furthermore, the second vacuum impregnation time is 1 hour to 12 hours; the drying temperature of the boron nitride ceramic substrate after the second vacuum impregnation is 100° C. to 200° C., and the drying time is 1 hour to 6 hours.

[0028] By adopting the above technical solution, by selecting a suitable impregnation time, it is possible to ensure that the silicone resin can fully penetrate into the micropores and cracks of the boron nitride ceramic matrix, forming a uniform coating and filling the pores; by selecting suitable drying parameters, the resin can be effectively cured without destroying the thermal stability of the boron nitride ceramic matrix.

[0029] A low water absorption boron nitride ceramic prepared by the preparation method of the low water absorption boron nitride ceramic as described above, wherein the low water absorption boron nitride ceramic is boiled in boiling water for 3 hours, and its water absorption is less than 0.2%.

[0030] Other features and corresponding beneficial effects of the present invention are described in the latter part of the specification, and it should be understood that at least some of the beneficial effects become obvious from the description in the specification of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a flow chart of the preparation process of low water absorption boron nitride ceramics. DETAILED DESCRIPTION

[0032] like Figure 1 As shown, the present invention is further described below in conjunction with specific embodiments and drawings.

[0033] A method for preparing boron nitride ceramics with low water absorption rate comprises the following steps:

[0034] S1: Boiling and drying the boron nitride ceramic substrate, and then performing a first vacuum impregnation in silica sol; the boron nitride ceramic substrate in this embodiment can be a boron nitride ceramic product that can be directly purchased on the market, or it can be a boron nitride ceramic product obtained by using raw materials such as boron oxide using existing preparation methods;

[0035] S2: removing the surface gel of the boron nitride ceramic substrate after the first vacuum impregnation; specifically, after the boron nitride ceramic substrate immersed in the silica sol is in-situ gelled, the temperature is gradually increased to dry and the surface gel is removed;

[0036] S3: sequentially sintering and vacuum impregnating the boron nitride ceramic substrate after removing the surface gel;

[0037] S4: Drying the boron nitride ceramic substrate after the second vacuum impregnation to obtain a boron nitride ceramic with low water absorption.

[0038] By adopting the above technical solution, the formed boron nitride ceramic matrix is ​​directly boiled, so that the boron oxide in the boron nitride ceramic matrix that is easily absorbing moisture is dissolved in boiling water and then dried, thereby reducing the water absorption rate of the boron nitride ceramic matrix to a certain extent. It is then placed in silica sol for immersion, so that the nano-silica particles in the silica sol are filled into the pores of the boron nitride, reducing the porosity of the boron nitride ceramic matrix; the silanol groups on the surface of the silica that are easily absorbing moisture are then removed by sintering, and the porosity of the boron nitride ceramic is further reduced by a second vacuum impregnation, so that the boron nitride has better moisture resistance; the entire process is simple, controllable, easy to implement, and conducive to industrial production. The prepared boron nitride ceramic has high density, low water absorption, excellent dielectric properties and thermal shock resistance, and can be used to prepare aerospace wave-transparent material components.

[0039] It is worth mentioning that a major highlight of this application is to directly process and improve the water absorption rate of both commercially available finished boron nitride ceramic substrates and already prepared boron nitride ceramic substrates. The existing mainstream methods for improving the water absorption rate of boron nitride ceramics include: improving the boron nitride ceramic raw material process; optimizing the sintering process; adding sintering aids, etc. However, improving the boron nitride ceramic raw material process firstly increases costs, because high-quality boron nitride raw materials are usually expensive, and some high-quality boron nitride raw materials may be scarce and difficult to obtain; and the impurity content in the raw materials has a significant impact on the performance of boron nitride ceramics. The need to control the purity of the raw materials means that the complexity and cost of raw material processing will increase; secondly, the synergistic effect between the raw materials to improve the water absorption rate of boron nitride ceramics is limited, and the effect is not very obvious. Optimizing the sintering process, whether optimizing the sintering temperature or adopting a more advanced sintering method, will increase costs; and the requirements for sintering equipment are high. The complexity of the sintering process may also lead to a decrease in process stability. For example, temperature fluctuations and inaccurate atmosphere control may affect the performance and quality stability of the final product, making it unsuitable for promotion and use. The addition of sintering aids often leads to increased costs, as the price of sintering aids is usually high, which will bring significant economic pressure to large-scale production. Moreover, the sintering aids may remain in the boron nitride ceramics during the sintering process, forming impurity phases, which in turn affect the specific properties of the boron nitride ceramics themselves.

[0040] In summary, the existing low water absorption rate operation of boron nitride will bring about the problem of increased cost and insignificant effect. Therefore, the present application directly improves the process on the already formed boron nitride ceramic matrix, greatly reducing the water absorption rate of the boron nitride ceramic without introducing complex equipment or operations, thus significantly reducing costs. Because the already formed boron nitride ceramic matrix will first be boiled, the boron oxide in the boron nitride ceramic matrix that is easy to absorb moisture will dissolve in the boiling water. This is the first step to improve the water absorption rate of the boron nitride ceramic matrix; then it will be placed in silica sol for the first vacuum impregnation, and the silica sol will be initially introduced into the surface and internal micropores of the boron nitride ceramic matrix to reduce the porosity of the boron nitride ceramic surface. This is the second step to reduce its water absorption rate; finally, through sintering and a second vacuum impregnation, the filling effect of silica sol on the boron nitride ceramic matrix is ​​strengthened. This is the third step to reduce its water absorption rate. The combination of these three steps ultimately makes the low water absorption rate boron nitride ceramic prepared by the present application have extremely low water absorption rate. In addition, the present application can also directly purchase finished boron nitride ceramic bodies with low water absorption rates, and further reduce the water absorption rate of the finished boron nitride ceramic bodies on the premise of low water absorption rate, so that it can meet the use scenarios in specific fields such as the manufacture of high-frequency microwave devices, greatly saving R&D time and efficiency, and with good results.

[0041] In one embodiment, the preparation of the silica sol in step S1 includes dissolving tetraethyl orthosilicate in ethanol and mixing and stirring to obtain a first mixed liquid, adding a second mixed liquid to the first mixed liquid, mixing and stirring, and then standing to obtain silica sol; the second mixed liquid is a mixture of hydrochloric acid and water.

[0042] Compared to traditional silica sol preparation methods, the resulting silica sol has a smaller particle size, reaching single-digit nanometers, while silica sols prepared using traditional methods are mostly in the tens of nanometers. The smaller particle size facilitates full filling of the pores of the boron nitride ceramic, effectively reducing porosity. The silica sol obtained using tetraethyl orthosilicate as the silicon source exhibits the best performance and a relatively stable process. Ethanol, added as a solvent for the hydrolysis of tetraethyl orthosilicate, does not hinder the hydrolysis and condensation reaction of tetraethyl orthosilicate and is safer than other alcohols. Adding water as a reactant for the hydrolysis of tetraethyl orthosilicate and hydrochloric acid as a hydrolysis catalyst promotes the full completion of the hydrolysis reaction and increases the solids content of the silica sol. Preparing the mixed solution in this order allows for a more complete reaction during the silica sol preparation process. The applicant has also conducted experiments demonstrating that the silica sol prepared above, before adding ammonia to adjust the pH, can be stored at room temperature for more than three months or even longer, demonstrating excellent stability and ease of storage, making it suitable for industrial production.

[0043] Preferably, the molar ratio of tetraethyl orthosilicate: ethanol: water: hydrochloric acid is set to 1:4-20:4-8:1.0×10-3-2.0×10-3; and the pH value of the second mixed solution is 2-3. It should be noted that the molar ratio of tetraethyl orthosilicate to water determines the rate and extent of the hydrolysis reaction; the molar ratio of ethanol as a solvent to tetraethyl orthosilicate affects the particle size of the silica sol; and the molar ratio of hydrochloric acid as a catalyst to tetraethyl orthosilicate has a significant impact on the rate of the hydrolysis reaction and the stability of the product. Because these four raw materials affect each other, the inventors of this application have rationally set the molar ratio of the raw materials to achieve a good balance between the particle size, distribution, stability, yield, and reaction rate of the silica sol.

[0044] Preferably, during the silica sol preparation process, the second mixed liquid is added to the first mixed liquid at a drop rate of 1 ml / min to 5 ml / min. Excessive drop rate of the second mixed liquid will cause the pH value in a local area of ​​the reaction system to drop rapidly, accelerating the polymerization reaction of silicate ions and potentially producing a large number of fine gel particles. These particles may quickly aggregate, resulting in an uneven gel structure and even precipitation. Excessive drop rate of the second mixed liquid will prolong the entire reaction time and reduce the silica sol formation rate. Furthermore, the mixing and stirring time after the second mixed liquid is added is 1 to 5 hours. Insufficient stirring time will result in uneven mixing of ethanol, tetraethyl orthosilicate, hydrochloric acid, and water, affecting the formation and properties of the silica sol. Excessive stirring time will increase energy consumption and reduce production efficiency.

[0045] In one embodiment, the specific process of removing the gel on the surface of the boron nitride ceramic substrate in step S2 is: adjusting the pH value of the silica sol to acidic to solidify the silica sol in situ gel, and then heating and drying to treat the gel on the surface of the boron nitride ceramic substrate.

[0046] In this embodiment, the silica sol is gelled and solidified in situ under acidic conditions, which accelerates the polymerization rate of silicates in the silica sol, which is conducive to the rapid formation of gel and improves the filling efficiency of the pores of the boron nitride ceramic matrix. In addition, during the in situ gel curing process, the bonding of the gel layer with the surface of the boron nitride ceramic matrix may be uniform and controllable, thereby avoiding damage to the surface of the boron nitride ceramic matrix during the subsequent cleaning process. At the same time, since the curing process does not require high temperature, the thermal impact on the boron nitride ceramic matrix is ​​relatively small, which helps to maintain its original physical and chemical properties.

[0047] Specifically, this embodiment uses a pH adjuster to adjust the pH of the silica sol to an acidic state. The pH adjuster is ammonia water with a concentration of 0.2 mol / L to 0.8 mol / L. After the addition of ammonia water, the pH value is adjusted to 5 to 7. By using ammonia water as a pH adjuster to solidify the silica sol in situ, the volatilization of the solvent during the drying process prevents the silica nanoparticles originally filling the pores from accumulating on the outer surface of the boron nitride, thereby reducing the filling rate of the ceramic's internal pores. Furthermore, ammonia water has low toxicity and volatility, causing relatively little environmental pollution. More importantly, after high-temperature treatment, ammonia water does not retain alkali metal cations that affect the dielectric loss of the boron nitride ceramic.

[0048] In one embodiment, after the silica sol in-situ gel is solidified, the temperature is raised from room temperature to 100°C; and the boron nitride ceramic matrix after removing the surface gel is sintered at a sintering temperature of 500°C to 900°C, a heating rate of 5°C / min to 20°C / min, and a holding time of 60min to 240min. Appropriate sintering parameters are determined to enhance the bonding force between the boron nitride particles and melt the particle surfaces, thereby forming a denser bond, which helps to improve the density and mechanical properties of the ceramic without incurring excessive production costs and energy consumption. The boron nitride ceramic matrix after the second vacuum impregnation is dried at a temperature of 100°C to 200°C and a drying time of 1h to 6h. The appropriate drying temperature and drying time ensure that while removing the solvent or moisture, the boron nitride ceramic will not cause thermal stress, cracking, or performance degradation due to excessive temperature.

[0049] In one embodiment, in step S3, the sintered boron nitride ceramic substrate is vacuum impregnated for a second time with a silicone resin, wherein the solid content of the silicone resin is 20% to 50% and the viscosity is 3 mPa•s to 25 mPa•s; and the time for the second vacuum impregnation is 1 hour to 12 hours.

[0050] Specifically, it is explained here that before the second vacuum impregnation, the boron nitride ceramic matrix has undergone the first vacuum impregnation, and the pores inside the boron nitride ceramic matrix have been basically filled with silica sol; therefore, the purpose of the second vacuum impregnation is to strengthen the filling effect of silica sol on the boron nitride ceramic matrix, which can ensure that more silica sol penetrates into the micropores and cracks of the boron nitride ceramic matrix, further reducing its water absorption rate; and the second vacuum impregnation uses silicone resin because the strong interaction between silicone resin and silica in silica sol can significantly improve the adhesion of the silicone resin layer to the surface of the boron nitride ceramic. This strong adhesion ensures that the resin layer can be firmly attached to the ceramic surface and is not easy to fall off or crack; at the same time, the close combination between silicone resin and silica forms a dense and continuous protective layer, which can effectively block the penetration of moisture and other corrosive media, further reducing the water absorption rate of the boron nitride ceramic.

[0051] If silica sol is used for the second impregnation, although silica sol can fill the micropores and defects on the surface of the boron nitride ceramic matrix, a single silica sol layer may not be able to completely prevent water penetration, and the purpose of low water absorption cannot be achieved; if organic resin is used for both vacuum impregnations, although the protective film formed by the silicone resin has high density and water resistance, an excessively thick resin layer will affect the air permeability and other properties of the boron nitride ceramic, making it impossible to use it in some high-frequency microwave devices and its applicability will be reduced.

[0052] A low-water-absorption boron nitride ceramic prepared using the preparation method of low-water-absorption boron nitride ceramic as described above, wherein the low-water-absorption boron nitride ceramic has a water absorption rate of less than 0.2%. While ensuring extremely low water absorption, it has good thermal shock resistance, a small dielectric constant, low dielectric loss, and good high-temperature oxidation resistance, and can be used in the field of high-temperature resistant and wave-transmitting ceramics.

[0053] Example 1

[0054] A method for preparing boron nitride ceramics with low water absorption rate comprises the following steps:

[0055] S1: A homemade boron nitride ceramic substrate with a density of 90% was boiled in boiling water for 5 hours and completely dried, and then completely immersed in silica sol for a first vacuum impregnation for 3 hours at a vacuum degree of -0.09 MPa. The silica sol was prepared by weighing 208 g of tetraethyl orthosilicate and dissolving it in 276 g of ethanol solvent. Then, a mixed solution of 72 g of water and 133 μL of concentrated hydrochloric acid was slowly added dropwise at a drop rate of 1 ml / min, wherein the molar ratio of tetraethyl orthosilicate: ethanol: water: concentrated hydrochloric acid was 1:6:4:1.6×10-3. After stirring for 2 hours, the mixture was allowed to stand to obtain a silica sol solution.

[0056] S2: After the boron nitride ceramic substrate immersed in the silica sol is in situ gelled, the temperature is gradually increased to dry and the surface gel is removed; that is, the pH value of the silica sol is adjusted to 6.5 using a 0.5 mol / L ammonia solution, and the silica sol is allowed to stand for 20 minutes to allow the silica sol to solidify in situ gel. The substrate is then gradually heated from room temperature to 100°C in an oven to dry, and the surface gel of the boron nitride ceramic substrate is removed;

[0057] S3: After removing the surface gel, the boron nitride ceramic substrate is dried in an oven at a temperature gradually increased from room temperature to 100°C, then placed in a muffle furnace and sintered at a heating rate of 8°C / min to 700°C for 150 minutes. After cooling, the substrate is immersed in a silicone resin with a solid content of 30% and a viscosity of 10 mPa·s under vacuum for 3 hours.

[0058] S4: The boron nitride ceramic substrate after the second vacuum impregnation is taken out and placed in a 120° C. oven for drying for 3 hours to obtain a low water absorption boron nitride ceramic.

[0059] The resulting low-water-absorption boron nitride ceramic was boiled in boiling water for 3 hours. Testing revealed a water absorption rate of only 0.03%, compared to 4.89% for commercially available untreated finished boron nitride ceramics. This indicates that the boron nitride ceramic's water absorption is significantly reduced after treatment. Furthermore, the resulting boron nitride ceramic was placed directly in a muffle furnace at 1000°C for 20 minutes and then removed and placed in cold water. No cracking occurred, indicating that the boron nitride ceramic exhibited excellent thermal shock resistance. Furthermore, the dielectric properties of the low-water-absorption boron nitride ceramic were tested, revealing a dielectric constant of 4.6 and a dielectric loss of 1.0×10-3, indicating that the boron nitride ceramic treated by this method still exhibits good dielectric properties.

[0060] Example 2

[0061] A method for preparing boron nitride ceramics with low water absorption rate comprises the following steps:

[0062] S1: A homemade boron nitride ceramic substrate with a density of 90% was boiled in boiling water for 5 hours and completely dried, and then completely immersed in silica sol for a first vacuum impregnation for 3 hours at a vacuum degree of -0.09 MPa. The silica sol was prepared by weighing 208 g of tetraethyl orthosilicate and dissolving it in 276 g of ethanol solvent. Then, a mixed solution of 72 g of water and 133 μL of concentrated hydrochloric acid was slowly added dropwise at a drop rate of 1 ml / min, wherein the molar ratio of tetraethyl orthosilicate: ethanol: water: concentrated hydrochloric acid was 1:6:4:1.6×10-3. After stirring for 2 hours, the mixture was allowed to stand to obtain a silica sol solution.

[0063] S2: cleaning the surface gel of the boron nitride ceramic substrate after the first vacuum impregnation; that is, gradually heating the gel in an oven from room temperature to 100° C. to solidify and dry the gel, and then cleaning the surface gel of the boron nitride ceramic substrate;

[0064] S3: After removing the surface gel, the boron nitride ceramic substrate is dried in an oven at a temperature gradually increased from room temperature to 100°C, then placed in a muffle furnace and sintered at a heating rate of 8°C / min to 700°C for 150 minutes. After cooling, the substrate is immersed in a silicone resin with a solid content of 30% and a viscosity of 10 mPa·s under vacuum for 3 hours.

[0065] S4: The boron nitride ceramic substrate after the second vacuum impregnation is taken out and placed in a 120° C. oven for drying for 3 hours to obtain a low water absorption boron nitride ceramic.

[0066] The obtained low water absorption boron nitride ceramics were boiled in boiling water for 3 hours. The water absorption of the obtained low water absorption boron nitride ceramics was tested to be 1.26%. This shows that compared with the silica sol gel curing by solvent evaporation, the silica sol in situ gel curing has a higher pore filling efficiency and a lower water absorption rate.

[0067] Example 3

[0068] A method for preparing boron nitride ceramics with low water absorption rate comprises the following steps:

[0069] S1: A homemade boron nitride ceramic substrate with a density of 95% was boiled in boiling water for 5 hours and completely dried, and then completely immersed in silica sol for the first vacuum impregnation for 2 hours at a vacuum degree of -0.09 MPa. The silica sol was prepared by weighing 208 g of tetraethyl orthosilicate and dissolving it in 368 g of ethanol solvent. Then, a mixed solution of 108 g of water and 150 μL of concentrated hydrochloric acid was slowly added dropwise at a drop rate of 2 ml / min, wherein the molar ratio of tetraethyl orthosilicate: ethanol: water: concentrated hydrochloric acid was 1:8:6:1.8×10-3. After stirring for 1 hour, the mixture was allowed to stand to obtain a silica sol solution.

[0070] S2: Cleaning the surface gel of the boron nitride ceramic substrate after the first vacuum impregnation; that is, adjusting the pH value of the silica sol to 7.0 using a 0.5 mol / L ammonia solution, and leaving it to stand for 10 minutes to allow the silica sol to solidify in situ, thereby cleaning the surface gel of the boron nitride ceramic substrate;

[0071] S3: After removing the surface gel, the boron nitride ceramic substrate is dried in an oven at a temperature gradually increased from room temperature to 100°C, then placed in a muffle furnace and sintered at a heating rate of 10°C / min to 750°C for 120 min. After cooling, the substrate is immersed in a silicone resin with a solid content of 35% and a viscosity of 10 mPa·s under vacuum for 3 h.

[0072] S4: The boron nitride ceramic substrate after the second vacuum impregnation is taken out and placed in a 150° C. oven for drying for 2 hours to obtain a low water absorption boron nitride ceramic.

[0073] The obtained low water absorption boron nitride ceramics were boiled in boiling water for 3 hours, and the water absorption of the obtained low water absorption boron nitride ceramics was tested to be only 0.13%.

[0074] Example 4

[0075] A method for preparing boron nitride ceramics with low water absorption rate comprises the following steps:

[0076] S1: A homemade boron nitride ceramic substrate with a density of 92% was boiled in boiling water for 5 hours and completely dried, and then completely immersed in silica sol for a first vacuum impregnation for 3 hours at a vacuum degree of -0.09 MPa. The silica sol was prepared by weighing 208 g of tetraethyl orthosilicate and dissolving it in 184 g of ethanol solvent. Then, a mixed solution of 72 g of water and 133 μL of concentrated hydrochloric acid was slowly added dropwise at a drop rate of 2 ml / min, wherein the molar ratio of tetraethyl orthosilicate: ethanol: water: concentrated hydrochloric acid was 1:4:4:1.6×10-3. The mixture was stirred for 2 hours and allowed to stand to obtain a silica sol solution.

[0077] S2: Cleaning the surface gel of the boron nitride ceramic substrate after the first vacuum impregnation; that is, adjusting the pH value of the silica sol to 6.0 using a 0.3 mol / L ammonia solution, and leaving it to stand for 3 hours to allow the silica sol to solidify in situ, thereby cleaning the surface gel of the boron nitride ceramic substrate;

[0078] S3: After removing the surface gel, the boron nitride ceramic substrate was placed in a muffle furnace and heated to 850°C at a rate of 10°C / min for 120 min. After cooling, it was immersed in a silicone resin with a solid content of 40% and a viscosity of 15 mPa·s under vacuum for 3 h.

[0079] S4: The boron nitride ceramic substrate after the second vacuum impregnation is taken out and placed in a 150° C. oven for drying for 2 hours to obtain a low water absorption boron nitride ceramic.

[0080] The obtained low water absorption boron nitride ceramics were boiled in boiling water for 3 hours, and the water absorption of the obtained low water absorption boron nitride ceramics was tested to be only 0.15%.

[0081] Example 5

[0082] A method for preparing boron nitride ceramics with low water absorption rate comprises the following steps:

[0083] S1: A homemade boron nitride ceramic substrate with a density of 90% was boiled in boiling water for 5 hours and completely dried, and then completely immersed in silica sol for a first vacuum impregnation for 3 hours at a vacuum degree of -0.09 MPa. The silica sol was prepared by weighing 208 g of tetraethyl orthosilicate and dissolving it in 552 g of ethanol solvent. Then, a mixed solution of 144 g of water and 266 μL of concentrated hydrochloric acid was slowly added dropwise at a drop rate of 2 ml / min, wherein the molar ratio of tetraethyl orthosilicate: ethanol: water: concentrated hydrochloric acid was 1:12:8:1.6×10-3. After stirring for 2 hours, the mixture was allowed to stand to obtain a silica sol solution.

[0084] S2: Cleaning the surface gel of the boron nitride ceramic substrate after the first vacuum impregnation; that is, adjusting the pH value of the silica sol to 5.8 using a 0.3 mol / L ammonia solution, and leaving it for 4 hours to allow the silica sol to solidify in situ, thereby cleaning the surface gel of the boron nitride ceramic substrate;

[0085] S3: After removing the surface gel, the boron nitride ceramic substrate was placed in a muffle furnace and heated to 850°C at a rate of 10°C / min for 180 min. After cooling, the substrate was immersed in a silicone resin with a solid content of 45% and a viscosity of 20 mPa·s under vacuum for 3 h.

[0086] S4: The boron nitride ceramic substrate after the second vacuum impregnation is taken out and placed in a 150° C. oven for drying for 2 hours to obtain a low water absorption boron nitride ceramic.

[0087] The obtained low water absorption boron nitride ceramics were boiled in boiling water for 3 hours, and the water absorption of the obtained low water absorption boron nitride ceramics was tested to be only 0.19%.

[0088] Comparative Example 1

[0089] Comparative Example 1 differs from Example 1 in that the finished boron nitride ceramic substrate was not boiled during the first vacuum impregnation, but was directly impregnated in silica sol. All other operating conditions and steps were the same as in Example 1. The boron nitride ceramic obtained in Comparative Example 1 was boiled in boiling water for 3 hours. The water absorption of the resulting boron nitride ceramic was 1.03%, indicating that the unboiled boron nitride ceramic substrate still contained boron oxide, which is easily hygroscopic. Therefore, further boiling in boiling water increases the water absorption of the boron nitride ceramic.

[0090] Comparative Example 2

[0091] The difference between Comparative Example 2 and Example 1 is that during the first vacuum impregnation, the boron nitride ceramic substrate was vacuum impregnated with an organosilicon resin, and the other operating conditions and steps were the same as those in Example 1. The boron nitride ceramic obtained in Comparative Example 2 was boiled in boiling water for 3 hours, and the water absorption rate of the obtained boron nitride ceramic was tested to be 2.28%. This shows that due to the self-lubricating effect of the boron nitride ceramic substrate itself and the weak interaction between the organosilicon resin and the boron nitride ceramic substrate, the pores in the boron nitride ceramic substrate could not be filled. However, silica sol was used for the first vacuum impregnation. After the nano-silica in the silica sol was filled with pores and sintered at high temperature, the resulting surface was silica, which had a stronger interaction with the organosilicon resin, resulting in a better pore filling rate.

[0092] The examples described in the present invention are merely descriptions of the preferred embodiments of the present invention and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a low water absorption boron nitride ceramic, characterized in that: The steps include: S1: Boil and dry the boron nitride ceramic substrate, and perform the first vacuum impregnation in silica sol; S2: removing the gel on the surface of the boron nitride ceramic substrate immersed in the silica sol; S3: sequentially sintering and vacuum impregnating the boron nitride ceramic substrate after removing the surface gel; wherein the second vacuum impregnation is performed on the boron nitride ceramic substrate after removing the surface gel using an organic silicone resin; S4: drying the boron nitride ceramic substrate after the second vacuum impregnation to obtain a boron nitride ceramic with low water absorption; The preparation of the silica sol in step S1 comprises dissolving tetraethyl orthosilicate in ethanol, mixing and stirring to obtain a first mixed solution, adding a second mixed solution to the first mixed solution, mixing and stirring, and then standing to obtain the silica sol; the second mixed solution is a mixture of hydrochloric acid and water; The specific process of removing the gel on the surface of the boron nitride ceramic substrate in step S2 is: adjusting the pH value of the silica sol to a weak acidity to solidify the silica sol in situ gel, and then heating and drying to treat the gel on the surface of the boron nitride ceramic substrate; using an alkaline solution pH regulator to adjust the pH value of the silica sol to a weak acidity, and the pH regulator is ammonia water, and the ammonia concentration is 0.2 mol / L to 0.8 mol / L, and after adding ammonia water, the pH value is adjusted to 5 to 7; In the step S3, the boron nitride ceramic matrix after removing the surface gel is sintered at a sintering temperature of 500°C to 900°C.

2. The method for preparing a low water absorption boron nitride ceramic according to claim 1, characterized in that: The molar ratio of tetraethyl orthosilicate: ethanol: water: hydrochloric acid is 1:4-20:4-8:1.0×10 -3 ~2.0×10 -3 ; and the pH value is 2-3 after adding the second mixed solution.

3. The method for preparing a low water absorption boron nitride ceramic according to claim 1, characterized in that: The second mixed liquid is added to the first mixed liquid at a dropping speed of 1 ml / min to 5 ml / min, and the mixing and stirring time after the second mixed liquid is added is 1 h to 5 h.

4. The method for preparing a low water absorption boron nitride ceramic according to claim 1, characterized in that: After the silica sol in-situ gel is solidified, the temperature is raised from room temperature to 100° C., and the boron nitride ceramic matrix after the surface gel is removed is sintered, the heating rate is 5° C. / min to 20° C. / min, and the insulation time is 60min to 240min.

5. The method for preparing a low water absorption boron nitride ceramic according to claim 1, characterized in that: In the step S3, the sintered boron nitride ceramic matrix is ​​vacuum impregnated for the second time with an organic silicone resin, wherein the solid content of the organic silicone resin is 20% to 50% and the viscosity is 3 mPa·s to 25 mPa·s.

6. The method for preparing a low water absorption boron nitride ceramic according to claim 5, characterized in that: The time of the second vacuum impregnation is 1 hour to 12 hours; the drying temperature of the boron nitride ceramic matrix after the second vacuum impregnation is 100° C. to 200° C., and the drying time is 1 hour to 6 hours.

7. A boron nitride ceramic with low water absorption prepared by the method for preparing a boron nitride ceramic with low water absorption as claimed in any one of claims 1 to 6, characterized in that: The water absorption rate of the low water absorption rate boron nitride ceramic is less than 0.2%.

Citation Information

Patent Citations

  • Method for preparing high-density boron nitride ceramic at low temperature

    CN118580080A

  • Boron nitride and silicon dioxide composite ceramic aerogel and preparation method thereof

    CN116425554A

  • Hole sealing moisture-proof anticorrosive composite coating material and its prepn process

    CN1931795A